THE CORRELATION OF KNOWLEDGE AND PARENT’S ATTITUDE TO THE INDEPENDENCY OF MILD MENTAL RETARDATION CHILDREND AT ELEMENTARY SCHOOL OF SPECIAL NEEDS CHILDEREN (SDLB) OF PROF. DR. SRI. SOEDEWI-MASJCHUN SOFWAN, SH, JAMBI 2017 - Anisa Anisa; Yunita Muliasari (Jurnal Akademika Baiturrahim Jambi, 2017)
Background:Mental retardation is a condition characterized by lower inteligence that causes an individual cannot learn and adapt to the needs of the community related to normal-considered capabilities.Method:The research is a quantitative research applying cross sectional method to identify the correlation of knowledge and parents’ Attitude to the independence of mental retardadion child. This research was conducted at SDLB Prof. Dr. Sri Soedewi Masjchun Sofwaan, SH from 1 to 9 of March, 2017. The number of samples used is 53 respondents with a total sampling technique. The instruments applied in data collection are research questionnaires, analyzed with univariat and bivariat applying chi square test. Result:The result of the analysis show that 75.5% has parent’s good knowledge, 52,8% has parent’s good attitude, 37.7% has the independence of mental retardation child. The result show that there is a correlation between knowledge (p-value = 0,021) and attitude (p-value = 0,004) with the independence of mental retardation children. It is sugested that SDLB coordinate cooperation with health educational institutes in order to provide guidance and counseling related to the service needs of Mental Retardation Children.